The clinical and morphological features of ovarian steroid cell tumors - E. V. Cherepanova; K. P. Laktionov; O. A. Anurova; A. I. Zotikov (ABV-press, 2014)
Ovarian steroid cell tumors are rare, unusual neoplasms. There is now no unified management tactics for patients with this pathology. The paper reviews the literature on the clinical and morphological characteristics, prognostic factors, diagnosis, and treatme nt in patients with ovarian steroid cell tumors.